PARAGENETIC ANALYSIS OF THE IRON SULFIDES AND OXIDES IN THE FE-S-O2-H2O SYSTEM - Ivanov I.P.; Kashirtseva G.A. (My University, 2001)
Mineral parageneses can be quantitatively analyzed now with computer programs and thermodynamic databases for minerals and aqueous solution species using D.S. Korzhinskii's theory. The procedure reduces such analysis to the inverse problem of using key parameters of the model system parageneses (T, P, acidity, solution composition and some others) for the study of the natural parageneses of initial rocks, ores, and facies. We studied the phase equilibria in the Fe-S-O2-H2O system that models the natural parageneses of iron sulfides and oxides using thermodynamic computer simulation. The system under study includes pyrite (Py), pyrrhotite (Po), hematite (Hem), magnetite (Mag), wustite (Wus), γ-Fe, and liquid sulfur (S1). The results are represented in the following diagrams: P-T diagrams for the closed dry system at T = 300-800°C and P = 0.5-5 kb and for the water-containing system at 300-500°C and P = Psat - 2 kb; logfO2 -T charts for the dry system open to oxygen at 300-800°C and for the water-containing system at 300-550°C, to P = 1 kb; logfO2-logmStotal for the system with water open to oxygen and sulfur at 300, 400, and 450°C, P = 1 kb. The introduction of 10 vol % of water into the system decreases the temperature of equilibria with liquid sulfur by 90-100°C. With increasing temperature, the total sulfur and iron concentration values rise by nearly three times for both closed and in open to oxygen systems but slightly decrease with rising pressure in the closed system. The total iron concentration varies in the system open to oxygen and sulfur by four to seven orders of magnitude in equilibria with pyrite (within its stability field). The studied solutions are acid, slightly acidic, or neutral. Calculated diagrams and data listed in tables allow to estimate, with some approximation, physicochemical parameters of deposition of iron sulfide and oxide parageneses related to acidic and neutral rock alteration.